EFEKTIVITAS MOLUSKISIDA BERBAHAN AKTIF NIKLOSAMIDA TERHADAP HAMA KEONG MAS (Pomacea canaliculata L.) PADA TANAMAN PADI - Sukis Ramadhan Putra; Saifuddin Hasjim (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2019)
Golden apple snails (Pomacea canaliculata L.) is one of important pests in rice cultivation that could making damage up to 90%. Some attempt to control that often done among them is mechanical control and chemical control by using molluscicide. One of type of molluscicide that is have predominence to control golden apple snail is molluscicide with active ingredient of niclosamide with character contact pesticide. The purpose of this research to know the effectivity of molluscicide niclosamide to control golden apple snail pest by treatment of various concentration. This research was conducted in the Lampeji Village, Jember using Completely Randomized Design with 6 treatment and 4 replication with concentration of molluscicide each of which is 0 ml/l, 1 ml/l, 2 ml/l, 3 ml/l, 4 ml/l, and 5 ml/l. The observed variables is mortality of golden apple snail, crops damage intensity, and total eggs group produced by golden apple snail. The result show that treatments of molluscicide with active ingredient of niclosamide could control golden apple snail with value 61,75% until 89,06%. The effective and efficient treatment is application treatment with value of concentration is 3ml/l with value 84,68%. Application of molluscicide with active ingredient of niclosamide also affected in crops damage intensity. The result of crops damage intensity is coming up with score from 8,28% until 23,03%.  Treatments of molluscicide with active ingredient of niclosamide overall could reduce potention of spawn eggs from golden apple snail pest. Eggs only found in control found 1 to 3 eggs group, whereas in P1-P5 no.